How do you solve using the completing the square method 0=3x^2-11x+6?
1 Answer
Apr 22, 2016
x=3
x=2/3
Explanation:
Given -
3x^2-11x+6=0
Divide each term by the coefficient ofx^2
x^2-11/3x+2=0
Take the constant term to the right
x^2-11/3x=-2
Divide the coefficient ofx by2 and add the
thus received value to both sides after squaring it.
x^2-(11/3xx1/2)x+(11/6)^2=-2+(11/6)^2
x^2-11/6x+121/36=-2+121/36
x^2-11/6+121/36=((-72)+121)/36=49/36
Take square root on both sides
(x-11/6)=+-sqrt(49/36)=+-7/6
x=7/6+11/6=(7+11)/6=18/6=3
x=-7/6+11/6=(-7+11)/6=4/6=2/3